Comparative dynamics of neutrophil mitochondrial activity across resveratrol delivery routes Panov Stanislav Alexandrovich - Panov Stanislav Alexandrovich; Makanova Ilona Olegovna; Mazneva Valeria Mikhailovna; Starodubtseva Daria Alexandrovna; Almasbekova Saule Serikbolkyzy; Voronov Denis Dmitrievich (Scientific Research and Experimental Development, 2026)
Neutrophils are a tractable biosensor for systemic mitochondrial status. We implemented a “mitochondrial passport” based on intravital fluorescence of live leukocytes and compared the impact of different trans-resveratrol delivery routes [1, 2]. Methods. Prospective pilot in healthy adults (27–38 y; n=74): pellets 200 mg (n=16; ~91% bioavailability), transdermal 100 mg (n=20; ~95%), capsules 4000 mg (n=18; ~+30% vs. standard), tablets 500 mg (n=20; ~1% effective, first-pass). Metrics at baseline and 1 month: leukocytes with mitochondrial accumulation (MA), spontaneous membrane damage (oxidative stress, OS), NBT (oxygen-energy metabolism), phagocytosis, and ribosomal accumulation [3].